An extremely rare cause of acute abdomen - Karaisli, Serkan; Er, Ahmet; Örsel, Atilla; Kamer, Erdinç (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Karaisli S, Er A, Örsel A, Kamer E. An extremely rare cause of acute abdomen. Turk J Gastroenterol 2017; 28: 311-3.